Cost of Optimum Design of Trunk Mains Network Using Geographical Information System and Support Programs (Journal of Engineering, 2015)
Sewer network is one of the important utilities in modern cities which discharge the sewage from all facilities. The increase of population numbers consequently leads to the increase in water consumption; hence waste water generation. Sewer networks work is very expensive and need to be designed accurately. Thus construction effective sewer network system with minimum cost is very necessary to handle waste water generation. In this study trunk mains networks design was applied which connect the pump stations together by underground pipes for too long distances. They usually have large diameters with varying depths which consequently need excavations and gathering from pump stations and transport the sewage to final waste water treatment plant. This situation urges to decrease the cost to minimum with efficient design of its performance. The aim of this research is minimizing the cost of all sewer components of trunk mains which are lengths, diameters, and volume of excavation with maintaining its performance.In this research, the utilization of GIS (Geographical Information System) software and VBA (Visual Basic for Application) which is integrated with GIS was used to implement the MST (Minimum Spanning Tree) algorithm to create a visual basic computer program that was used to find the minimum total lengths of the trunk mains in a sewer network.This method was applied on selected areas in Al-Mansour municipality where there is an existing sewer system containing trunk mains and pump stations. Total lengths of the existing trunk mains are calculated and later, the proposed method was implemented to find the minimum total lengths, with a difference in total lengths of (12601 m).The new network used to design a proposed sewer system using the computer program SewerGemsV8i, which can be integrated with GIS. New pipes diameters and slopes were calculated by supplying the necessary information that is needed by the computer program.New sewer system was designed which gave more reliable and economical aspects than the existing one. These results clearly show that when comparing the costs.